The Effect Intermittent Fasting On Clinical Markers Among Patients With Type 2 Diabetes Mellitus: Systematic Review - Inayati, Aini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: To evaluation of evidences of the effect of intermittent fasting on clinical marker among type 2 Diabetes. Methods: Systematic review analysis has performed to identify relevant papers that addressed the research question and a clearly articulated question that defines, selects and critically reviews all relevant research using systematic and reproducible methods. Results: A total of eight articles had six review studies that consisted report of HbA1c level was significantly affect reduce by of intermittent fasting in type 2 diabetes, intermittent fasting had negatively affected body mass index, and had positively average effect on cholesterol among patients with diabetes type 2 Conclusion: Based on the data presented in this report, intermittent fasting is recommended to be used as an alternative to regular calorie restriction for individuals involved in improving body structure and overall well-being who have type 2 diabetes